Plasma polymer surface modified expanded polytetrafluoroethylene promotes epithelial monolayer formation in vitro and can be transplanted into the dystrophic rat subretinal space. (23rd November 2020) - Nian, Shen; Kearns, Victoria R.; Wong, David S. H.; Bachhuka, Akash; Vasilev, Krasimir; Williams, Rachel L.; Lai, Wico W.; Lo, Amy; Sheridan, Carl M.
Abstract: The aim of this study was to evaluate whether the surface modification of expanded polytetrafluoroethylene (ePTFE) using an n ‐heptylamine (HA) plasma polymer would allow for functional epithelial monolayer formation suitable for subretinal transplant into a non‐dystrophic rat model. Freshly isolated iris pigment epithelial (IPE) cells from two rat strains (Long Evans [LE] and Dark Agouti [DA]) were seeded onto HA, fibronectin‐coated n ‐heptylamine modified (F‐HA) and unmodified ePFTE and fibronectin‐coated tissue culture (F‐TCPS) substrates. Both F‐HA ePTFE and F‐TCPS substrates enabled functional monolayer formation with both strains of rat. Without fibronectin coating, only LE IPE formed a monolayer on HA‐treated ePTFE. Functional assessment of both IPE strains on F‐HA ePTFE demonstrated uptake of POS that increased significantly with time that was greater than control F‐TCPS. Surgical optimization using Healon GV and mixtures of Healon GV: phosphate buffered saline (PBS) to induce retinal detachment demonstrated that only Healon GV:PBS allowed F‐HA ePTFE substrates to be successfully transplanted into the subretinal space of Royal College of Surgeons rats, where they remained flat beneath the neural retina for up to 4 weeks. No apparent substrate‐induced inflammatory response was observed by fundus microscopy or immunohistochemical analysis, indicating the potential of this substrate for future clinical applications.